Web-based intelligent e-learning systems technologies and applications - Ma, Zongmin 1965-.; Gale Group (Hershey, Penn. Information Science Pub., 2006)
"This book offers a complete understanding of the notions, techniques, and methods related to the research and developments of web-based e-learning systems"--Provided by publisher.
Adaptive support for inductive reasoning ability / Kinshuk, Taiyu Lin, Paul McNab -- Automatic authoring of adaptive educational hypermedia / Alexandra I. Cristea, Craig Stewart -- Automatic learning object selection and sequencing in web-based intelligent learning systems / Pythagoras Karampiperis, Demetrios Sampson -- Building virtual learning communities / Naomi Augar ... [et al.] -- A conceptual architecture for the development of interactive educational multimedia / Claus Pahl -- Considering students' emotions in computer-mediated learning environments / PatriÌ?cia Augustin Jaques, Rosa Maria Viccari -- Defining personalized learning views of relevant learning objects in a collaborative bookmark management system / Antonella Carbonaro -- Hyperbook features supporting active reading skills / Tom Murray -- Knowledge representation in intelligent educational systems / Ioannis Hatzilygeroudis, Jim Prentzas -- Modeling of adaptive tutoring processes / Alke Martens -- Ontologies and contracts in the automation of learning object management systems / Salvador Sanchez-Alonso, Miguel-Angel Sicilia, Elena Garci?a-Barriocanal -- The role of metadata in e-learning systems / Juha Puustjarvi -- AWLA : a writing e-learning appliance / Manuel Ortega Cantero, Pedro Pablo Sanchez-Villalon -- Effects of teaching science through immersive virtual environments / Lisa M. Daniels ... [et al.] -- An integrated platform for educational virtual environments / C. Bouras ... [et al.] -- Intelligent and adaptive web-based instruction / Beverly Woolf, Mia Stern -- A special purpose e-learning environment : background, design and evaluation / Maria Kordaki.
Electronic reproduction.
Keywords: Web-based instruction -- Design; Education -- Computer network resources; Educational technology; Electronic books